Students' Perspective on English Language Skills: Challenges and External Factors - Sya, Mega Febriani; Amir, Fachru Razy; Fitrah RG, Zahra (International Journal of Language Education, 2025)
This study aimed to examine the influence of educational background on students' perspectives on English-language ability in Indonesia by analyzing language skills and the factors that both challenge and support their development. This study employed a qualitative method, and descriptive analysis was conducted using a questionnaire completed by 34 students from high school, vocational high school, Madrasah, and boarding school. Meanwhile, the interview data were analyzed using thematic analysis techniques. The findings showed that students from high schools and vocational high schools excelled in Writing and Reading.  School curricula place greater emphasis on writing skills than on oral communication skills. Reading proficiency is relatively high, indicating that students have access to and reading habits with English-language texts, including textbooks, articles, and other media. On the other hand, listening and speaking remain significant challenges for students, likely due to limited direct or audio exposure to English conversations and, for speaking, to limited practice in academic settings. External factors, such as exposure to English-language media, improve students' English-language skills, although psychological support and English-course experiences remain limited. This study suggests the need to improve language skills and to develop an environment that supports more active English-language practice.